L-cystein modified bentonite-cellulose nanocomposite (cellu/cys-bent) for adsorption of Cu2+, Pb2+, and Cd2+ ions from aqueous solution. Issue 3 (11th February 2016) - Ahmad, Rais; Hasan, Imran
ABSTRACT: In this study, L-cystein modified bentonite-cellulose (cellu/cys-bent) nanocomposite was synthesized and characterized by XRD, FTIR, SEM with EDS, TGA, and TEM techniques. In order to optimize the process the effect of various operational parameters such as pH, adsorbent dosage, contact time, and temperature were also investigated. The adsorption experiments were carried out in initial concentrations range of 20-100 mg L −1 and the adsorbent affinity for metal ions was found to be in order of Cu 2+ > Pb 2+ > Cd 2+ . The optimum pH for adsorption of Cu 2+ and Cd 2+ was observed at 5 while for Pb 2+ it was pH 6. Based on the Langmuir model, the maximum adsorption capacity of Cu 2+, Pb 2+, and Cd 2+ at 50 ᴼ C was found to be 32.36, 18.52, and 16.12 mg g −1, respectively. The Langmuir isotherm and pseudo-second order model were found to be better fitted than the other isotherms and kinetic models. The results of thermodynamic parameters confirmed the process to be endothermic and spontaneous in nature.